Imidazolinium‐based Multiblock Amphiphile as Transmembrane Anion Transporter. Issue 2 (9th December 2020) - Mori, Miki; Sato, Kohei; Ekimoto, Toru; Okumura, Shinichi; Ikeguchi, Mitsunori; Tabata, Kazuhito V.; Noji, Hiroyuki; Kinbara, Kazushi
Abstract: Transmembrane anion transport is an important biological process in maintaining cellular functions. Thus, synthetic anion transporters are widely developed for their biological applications. Imidazolinium was introduced as anion recognition site to a multiblock amphiphilic structure that consists of octa(ethylene glycol) and aromatic units. Ion transport assay using halide‐sensitive lucigenin and pH‐sensitive 8‐hydroxypyrene‐1, 3, 6‐trisulfonate (HPTS) revealed that imidazolinium‐based multiblock amphiphile (IMA ) transports anions and showed high selectivity for nitrate, which plays crucial roles in many biological events. Temperature‐dependent ion transport assay using 1, 2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphocholine (DPPC) indicated that IMA works as a mobile carrier. 1 H NMR titration experiments indicated that the C2 proton of the imidazolinium ring recognizes anions via a (C−H) + ⋅⋅⋅X − hydrogen bond. Furthermore, all‐atom molecular dynamics simulations revealed a dynamic feature of IMA within the membranes during ion transportation. Abstract : An imidazolinium‐based multiblock amphiphile, a mobile carrier capable of transmembrane anion transport with selectivity for nitrate, was developed. It recognizes anions via (C−H) + ⋅⋅⋅X − hydrogen bond of proton at C2 position of the imidazolinium ring.